Analisis Term and Condition dalam Akses Digital Platform Ditinjau dari Hukum Positif - Indrawan, Cecilia Vania; Tjoneng, Arman (Bhirawa Law Journal, 2024)
Digital platforms make it easy for people to do activities. But behind the convenience provided there are several problems that can endanger users. There is a need for regulations that specifically regulate the Protection of User Personal Data. Therefore, Law No. 27 of 2022 concerning Personal Data Protection was born. The research method used in this research is the Normative Juridical method. Based on the results of the research, the Personal Data Protection Law is sufficient to provide protection to users, especially due to data leaks that should be protected in accordance with the terms and conditions agreed and will be protected by the platforms. But it needs the help of other laws in protecting it, such as the 1945 Constitution which is the initial guideline, the ITE Law which regulates business actors, namely digital platforms that provide facilities for users to provide good and correct information as well as for users not to misuse these platforms, Permenkominfo which plays a role in supervising each platform to comply with predetermined provisions, the Civil Code as sanctioning articles, and the Consumer Protection Law which functions as the front guard to protect users, because there are threats to personal data security.